Knowledge, attitudes and practices related to oral health in participants of the Institutional Program for the Inclusion of People with Cognitive Disabilities in Higher Education at the University of Costa Rica = Conocimientos, actitudes y prácticas relacionadas con la salud oral en participantes del Programa Institucional de Inclusión de Personas con Discapacidad Cognitiva a la Educación Superior de la Universidad de Costa Rica - Garita Herrera, Andrea 1990-
People with cognitive disabilities face multiple challenges concerning oral health and frequently show oral tissue decay because of the barriers society imposes upon them, and due to financial issues, professional and family lack of knowledge, limitations regarding access to services, lack of empowering-driven actions, among others. Positive knowledge, attitudes and practices regarding oral health, developed during the course of a lifetime, help in preserving good health. The aim of the current study is to describe oral health knowledge, attitudes and practices in people with cognitive disabilities participating in the Institutional Program for the Inclusion of People with Cognitive Disabilities in Higher Education at the University of Costa Rica (PROIN, in Spanish), during 2021. A descriptive study with mixed focus was performed; a representative sample comprised of 86 students enrolled in PROIN was used for the quantitative approach, while the qualitative approach used a criteria sample along with an opinion sample, limiting size due to information overload. The survey, along with its corresponding questionnaire and the semi-structured interview, were used as data gathering techniques. It was evidenced that certain issues need to be readdressed, such as bleeding gums, the importance of preserving dental pieces, as well, the practice of flossing, which many students expressed difficulties doing. Good attitudes were found, such as dentist visits; however, access barriers for this population must be overthrown. This article showed the importance of training professionals in disabilities as well as developing oral health promotion programs aimed at people with cognitive disabilities.